Variasi Morfologi Pteris Vittata l. (Pteridaceae; Pteridophyta) dan Korelasinya dengan Ketinggian Lokasi Tempat Tumbuhnya di Jawa - Mumpuni, Mugi (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2016)
Pteris vittata has a high morphological variation and it has wide geographic regions around the world . Study of morphology and its correlation with with altitude of plant origin area in Java is very little informed. This aims of this research were first to study the diversity of morphological characters of P. vittata from Java; and to know the correlations among morphological characters to the plant orignated altitute; This study was conducted from September 2012 until September 2013. Plants materials wereÂ collected by exploration method.Â Morphological observations carried out on 130 individuals that had been collected from West Java, Central of Java and Yogyakarta in various altitude areas. Pteris vittata from Java Island varied in the morphological characters. The varied in the morphological characters i.e. size and shape of fronds, pinnae and apical segment. Variations in morphology was not correlated with altitude of plant origin area. Taxonomycally, P. vittata in Java can be divided into two groups infraspecies, namely P.vittata subspecies vittata and P.vittata subspecies emodi.